Modeling and analysis of the LC filter-integrated quasi Z-source indirect matrix converter for the wind energy conversion system - Maheswari, K. T.; Kumar, C.; Balachandran, Praveen Kumar; Senjyu, Tomonobu (Frontiers in Energy Research, 2023)
A Quasi Z-Source Indirect Matrix Converter (QZSIMC) is proposed in this paper for Permanent Magnet Generator (PMG) based Direct Drive Wind Energy Conversion Systems (DDWECS) to enhance the gain and also to maintain the voltage at the output under various loading conditions. The QZSIMC comprises three Quasi Z-Source (QZS) networks connected between PMG and load through a three-phase Indirect Matrix Converter (IMC). In this paper, modeling, control, and analysis of QZSIMC have been carried out. A closed-loop control system is designed to sustain constant parameters at the output. The analysis of the proposed QZSIMC is done and proved that the system remains stable for all ranges of output power without using the filter. The proposed QZSIMC based DDWECS, along with Modified Space Vector Pulse Width Modulation (MSVPWM) Control Scheme, is to be modeled using MATLAB environment. To validate the simulation results, a 1kW, 415V, 50Hz experimental setup with an FPGA SPARTAN-6 processor has been developed in the laboratory for QZSIMC. The results are investigated based on Switching Stress, Boost Factor, Total Harmonic Distortion, and Power Conversion Efficiency.